Development of protease deficient Meyerozyma guilliermondii strain so for overexpression of thermostable T1 lipase - Lorrine, Okojie Eseoghene (2022)
Meyerozyma guilliermondii strain SO, a novel expression host was found to belong to the Meyerozyma species complex called the CTG clade yeasts that exhibited a particular genetic code where the universal leucine CUG codon was predominantly translated as serine and rarely as leucine. In previous study, M. guilliermondii strain SO, was used as an expression host for thermostable T1 lipase from Geobacillus zalihae under the regulation of an alcohol oxidase promoter (pAOX1) with a low yield recorded. This could be due to the CUG ambiguity as well as the vacuolar protease(s) of strain SO secretory system which were potential bottleneck during the production of recombinant secretory proteins in yeast systems. In this study, two strategies had been implemented to maximize the secretory potential of strain SO by firstly carrying out a codon optimization of the recombinant protein using the M. guilliermondii codon usage and secondly, by identification and disruption of the critical putative vacuolar proteases of strain SO using Cre-Lox recombination technique. Transformation and expression of a codon optimized T1 lipase gene cloned onto pPICZαB vector (pPICZαB/T1SLip) was performed in strain SO, where previous recombinant plasmid pPICZαB/T1 was used as positive control. However, there was no significant difference in the expression levels between the wild type and the codon optimized T1 lipase gene. Then, hidden Markov model (HMM) software was used to search for the possible vacuolar proteases (hits) in strain SO proteome. From the results, a vacuolar aspartic protease (PEP4) with 97.55% identity to Meyerozyma sp.JA9 and a serine protease (PRB1) with 70.91% identity to Candida albicans, were found in strain SO proteome. Evolutionary analysis, further confirmed homology with other yeast vacuolar proteases. In addition, the structures of strain SO PEP4 and PRB1 were predicted using Phyre2 and validated by PROCHECK, ERRAT and Verify3D, with a comparability of 91.1% and 85.8% with their respective templates from Ramachandran plots prediction. Further structural analysis revealed their essential catalytic residues and a protein-ligand interaction, depicted their catalytic mechanisms. Next, Cre-Lox recombination technique was initiated to delete the identified PEP4 and PRB1 genes of strain SO. The upstream and downstream of the target genes were cloned to the promoter and terminator regions of the SAT1 flipper cassette respectively. Next, positive transformants were obtained after 24 h of growth incubation time on a selective medium containing 200 μg/mL of nourseothrincin (NAT). Finally, optimization of recombinant proteins (T1 and T1SLip lipase) expression with the developed mutants in shake flask was carried out using recombinant pPICZαB/T1/APM-(APMSO2), pPICZαB/T1/SPM-(SPMSO2), pPICZαB/T1/DPM-(DPMSO2), pPICZαB/T1SLip/APM-(APM_807), pPICZαB/T1SLip/SPM-(SPM_089) and pPICZαB/T1SLip/DPM-(DPM_0789). Media YPTG (Yeast extract-Peptone-Tryptic soy broth and glycerol) and YPTM (Yeast extract-Peptone-Tryptic soy broth and methanol) were used to grow and induce the recombinant strains for the expression of T1 lipase with 0.5% (v/v) methanol induction shown to be the optimum concentration with an optimum induction time of 12 h interval for 3-5 days. The highest expression yield was recorded with the APMSO2 (1.12 U/mL at 72 h). It is interesting to note that, the optimum T1 lipase expression in APMSO2 was a 1000% increase compared to the wild type SO2. In conclusion, the codon optimized T1 lipase (T1SLip) was sucessfully cloned into the vector backbone of pPICZαB and expressed in strain SO. The two critical putative vacuolar proteases (PEP4 and PRB1) were successfully identified in strain SO. The structures of strain SO PEP4 and PRB1 from strain SO were successfully predicted and analyzed for their catalytic functions. The deletion of the vacuolar protease genes were also successful and the developed mutants could express the codon optimized T1 lipase (T1SLip) and T1 (wild type) lipase genes with a 1000% increase recorded from APMSO2 compared to the wild type SO2.